The effects of acarbose treatment on cardiovascular risk factors in impaired glucose tolerance and diabetic patients: a systematic review and dose–response meta-analysis of randomized clinical trials - Zamani, Mohammad; Nikbaf-Shandiz, Mahlagha; Aali, Yasaman; Rasaei, Niloufar; Zarei, Mahtab; Shiraseb, Farideh; Asbaghi, Omid (Frontiers in Nutrition, 2023)
Acarbose (ACB) seems to be an effective drug in the management of cardiovascular risk factors.However, no previous meta-analysis of randomized controlled trials (RCTs) has been done to evaluate the effects of ACB on cardiovascular risk factors on impaired glucose tolerance (IGT), type 2 diabetes (T2D), and type 1 diabetes mellitus (T1D).Comprehensively searched electronic databases including Scopus, Web of Science, and PubMed for RCT for related keywords up to September 2022. A random-effects model was used to estimate the weighted mean difference (WMD) and 95% confidence interval (CI). The pooled analysis demonstrated ACB treatment had a significant effect on fasting blood glucose (FBG) [WMD= -3.